Concept and Strategy for Implementing the National Action Plan on Health Literacy in Germany. (30th September 2020) - Schaeffer, D; Berens, E; Gille, S; Hurrelmann, K; Bauer, U
Abstract: Background: In Germany, the development of the National Action Plan on Health Literacy (NAP) was triggered by results of the HLS-GER, the first representative study on HL in Germany, showing that more than half of the German population perceive great problems in processing health information. In response to this, a group of 15 experts from academia, practice and policy worked together on a first draft of the NAP, which was refined based on various stakeholder consultations and finally published in 2018. The plan focuses on four areas of action and initially presents 15 specific recommendations to strengthen health literacy in Germany following five key principles. After the delivery to the Federal Minister of Health in 2018, it quickly became clear that the action plan and its recommendations need additional tools for implementation. Therefore, a systematic implementation strategy was developed. Methods: Core elements of the implementation strategy were a systematic dissemination of the plan as well as workshops with important stakeholders from policy, associations, patient and self-help organisations. The aim of the workshops was it to concretise single recommendations of the NAP and to develop additional tools to implement them in specific fields of actions. The workshops led to policy papers, which were consented by a group of stakeholders and again disseminated broadly. Results: Through numerous publications and presentations in different contexts the NAP received great attention. Furthermore, seven workshops and one international symposium were conducted focussing on single recommendations of the NAP, each leading to policy papers. The workshops and policy papers contributed to identification with the NAP and motivated the development of tools to promote health literacy. Conclusions: The implementation strategy was effective as many stakeholders could be involved. It is also resource and time consuming which needs to be considered in project planning.